Studi Etnobotani Tumbuhan Pewarna Alami di Desa Raut Muara Kabupaten Sanggau - Riani, Sapa; Syamswisna, Syamswisna; Mardiyyaningsih, Asriah Nurdini (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
ABSTRACT The use of synthetic dyes can trigger health and environmental problems. Natural dyes are one of the innovations to replace the use of synthetic dyes because they are non-toxic and environmentally friendly. The people of Raut Muara Village, Sanggau Regency utilize several plants as natural dyes such as tipu' (Etlingera linguiformis (Roxb.) R.M.Sm) which is used as a food dye, kecombrang (Etlingera elatior (Jack)) as a beverage dye, red bajakah (Spatholobus ferrugineus Zoll.&Moritzi)Benth.) as a cosmetic, and yellow root (Arcangelisia flava (L.) Merr) as a fabric dye. This study aims to increase public knowledge about the types, parts of plants used and processing methods carried out by the people of Raut Muara Village. The method used in the research is descriptive method and data collection techniques by triangulation which is a combination of interviews, observation and documentation. Determination of informants using purposive sampling technique with 53 informants. The results of the study obtained 26 plant species from 22 families that are utilized by the leaves, fruit, seeds, and roots. Keywords: Ethnobotany, Natural coloring, Raut Muara VillageABSTRACT The use of synthetic dyes can trigger health and environmental problems. Natural dyes are one of the innovations to replace the use of synthetic dyes because they are non-toxic and environmentally friendly. The people of Raut Muara Village, Sanggau Regency utilize several plants as natural dyes such as tipu' (Etlingera linguiformis (Roxb.) R.M.Sm) which is used as a food dye, kecombrang (Etlingera elatior (Jack)) as a beverage dye, red bajakah (Spatholobus ferrugineus Zoll.&Moritzi)Benth.) as a cosmetic, and yellow root (Arcangelisia flava (L.) Merr) as a fabric dye. This study aims to increase public knowledge about the types, parts of plants used and processing methods carried out by the people of Raut Muara Village. The method used in the research is descriptive method and data collection techniques by triangulation which is a combination of interviews, observation and documentation. Determination of informants using purposive sampling technique with 53 informants. The results of the study obtained 26 plant species from 22 families that are utilized by the leaves, fruit, seeds, and roots.Keywords: Ethnobotany, Natural coloring, Raut Muara Village